A FOCUS ON THE LANDSCAPE MOSAICS: VEGETATION MAP OF “SERRA ROCCA CHIARANO – MONTE GRECO” S.C.I (ABRUZZO, CENTRAL APENNINES) - D'ANGELI, D.; TESTI, A.; FANELLI, G.; BIANCO, P.M. (Annali di Botanica, 2011)
Aim of this paper is to produce a GIS vegetation map of a high mountain area in Central Apennines applying the landscape ecological approach. The study area is Greco Mountain and Rocca Chiarano mountain ridge (Abruzzo, Central Italy), a calcareous system with very high biodiversity, designated as a Site of Community Importance in the frame of the Directive 92/43/EEC. 120 phytosociological relevés, sampled in 2005-2009 from May to October, were subjected to Cluster Analysis and 18 vegetation types, at the association level, have been distinguished. Ten of these associations are not represented in the vegetation map, due to their small-scale extent. Two alternative methods for vegetation mapping of the area, i.e. the standard synphytosociological and the landscape mosaic approach are briefly discussed. The former cannot be applied to the study area due to recent very intensive disturbance and ongoing rapid dynamics. The mosaic types represented in the map have been individuated on the basis of the occurrence of dominant species. Two mosaic categories have been identified: morphological and dynamic mosaic resulting from the different importance of natural factors vs. anthropogenic disturbance. Advantages and usefulness of the mapping approach adopted here are discussed as tools to detect, describe and represent complexity of ecosystem relationships.